Carta de Roberto H. Todd a Mará Cadilla de MArtínez - Todd, Roberto H.; Cadilla de Martínez, María (My University, 1935)
Artículo sobre Lola Rodríguez de Tió.
Keywords: Rodríguez de Tió, Lola, 1843-1924